Impact of 3% Simvastatin Topical Cream on the Healing of Bedsores: A Double-Blinded Randomized Clinical Trial: Simvastatin topical cream and bedsores - Aghajari, Afarin; Moaref, Mahgol; Ganji, Reza (Iranian Journal of Pharmaceutical Sciences, 2024)
Since the prevalence of pressure ulcers has been increasing in recent years, they need a new and efficient treatment. The pleiotropic effects of statins can be used for this purpose. This study aimed to evaluate the appropriate formulation of 3% simvastatin (SIM) topical cream and its effect on the healing of bedsores. At first, the appropriate formulation of SIM topical cream was investigated. In a randomized, double-blind trial, 42 patients were divided into two groups: placebo and SIM cream, and used these creams for three weeks, once every 12 hours on a clean bedsore. Bedsore dimensions were measured at the beginning and end of the study. Seventy-seven percent of patients in the SIM group and 35% in the placebo group had more than 20% healing of bedsores. Age (P=0.03), gender (P=0.01), statin use (P=0.04), and diabetes (P=0.04) had statistically significant impacts on bedsore healing. Also, better wound healing in the non-diabetic patients was observed. It seems that the topical cream of SIM significantly affects the healing of bedsores and can also be used in bedsores of diabetic patients. In diabetic patients with bedsores, blood sugar control through nutritional counseling and consumption of regular diabetic medication seems to be very effective and efficient.